2014
DOI: 10.1007/s10157-014-1000-3
|View full text |Cite
|
Sign up to set email alerts
|

The biological significance of angiotensin-converting enzyme inhibition to combat kidney fibrosis

Abstract: Both angiotensin-converting enzyme inhibitor (ACE-I) and angiotensin II receptor blocker have been recognized as renin-angiotensin system (RAS) inhibitors. These two RAS inhibitors are rarely recognized as drugs with distinct pharmacological effects in the clinic or most clinical trials. Some preclinical basic research and clinical trials indicate that ACE-I might display superior organ-protective effects, especially anti-fibrotic effects. Such anti-fibrotic effects of ACE-I could be associated with an endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 105 publications
0
7
0
1
Order By: Relevance
“…Among RAS inhibitors, angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin II type 1 receptor blockers (ARB) are two major drug classes prescribed to delay diabetic nephropathy progression [ 6 , 7 ]. These two drug classes may exhibit similar renoprotective effects but also may display significant differences in organ protection from diabetes-associated damage [ 7 11 ]. It is well known that the maximum dose of ACE-I, which abolishes circulatory angiotensin II, cannot inhibit local angiotensin II production in renal tubules [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among RAS inhibitors, angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin II type 1 receptor blockers (ARB) are two major drug classes prescribed to delay diabetic nephropathy progression [ 6 , 7 ]. These two drug classes may exhibit similar renoprotective effects but also may display significant differences in organ protection from diabetes-associated damage [ 7 11 ]. It is well known that the maximum dose of ACE-I, which abolishes circulatory angiotensin II, cannot inhibit local angiotensin II production in renal tubules [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are two catalytic domains, N-terminal and C-terminal, in the ACE [ 7 ]. Angiotensin I is mainly metabolized into angiotensin II at the C-terminal catalytic site of ACE; the N-terminal specific substrate N-acetyl-seryl-aspartyl-lysyl-proline (AcSDKP) is the antifibrotic peptide [ 15 ] synthesized through protein processing, which is generated by prolyl oligopeptidase from the precursor peptide thymosin β 4 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether the increase of circulating Ac-SDKP mediates some of the beneficial effects of ACE inhibitor treatment in CKD. 54 A study investigating the role of endogenous Ac-SDKP in fibrosis demonstrated that downregulation of Ac-SDKP in rats by administrating a POP inhibitor (S17092, 40 mg/kg/day) increased collagen deposition and promoted cardiac and renal perivascular fibrosis and glomerulosclerosis. 55 These findings suggested that exogenous Ac-SDKP could have an antifibrotic effect.…”
Section: The Therapeutic Potential Of Thymosin-b4 and Its Derivativesmentioning
confidence: 99%
“…Even with the use of such renin-angiotensin system inhibitors, we still have no clear answer as to whether angiotensinconverting enzyme inhibitors and angiotensin receptor blockers have the same effects. 8 However, there is still some hope to combat diabetes. Recently, both preclinical and clinical studies have demonstrated some potential for incretin-based therapies to combat kidney diseases in diabetic patients.…”
Section: Acknowledgmentsmentioning
confidence: 99%